Reading Pedagogy in EFL Classes for Students with albinism: A case study - Dossou Flavien LANMANTCHION (Akofena)
Abstract: Benin Republic encounters socio economic challenges that impact access to education for all children, particularly, those with disabilities like albinism. This paper looked into the practices of teachers in reading and perceptions of students with albinism in English language classes in the Republic of Benin. The study explores the gaps that need to be addressed for students with albinism to better reach their potential in reading. To reach this purpose, data were collected mainly through unstructured interviews to10 participant teachers who have once taught students with albinism and a uniform questionnaire to fifty-six (56) students with albinism. The study has revealed a lack of a specified special education curriculum and adapted reading materials, inadequate training system, teachers’ comfort levels and beliefs, selection of appropriate reading texts and designing tasks for teaching reading and non-adapted reading assessment. The researcher suggests an adapted curriculum and a series of training sessions for EFL teachers to enhance reading instructional practices for students with albinism and actually increase teachers’ comfort levels against students with albinism.